Anti-Diabetic Effect of Snake Fruit Skin Extract in Alloxan-Induced Wistar Rat - Marlinda Marzuki; Ermi Girsang; Ali Napiah Nasution; I Nyoman Ehrich Lister (International Journal of Health and Pharmaceutical (IJHP), 2022)
Basic Health Research Report shows that an average prevalence of diabetes mellitus (DM) in urban areas is 5.7% in the population aged over 15 years. Many studies have been conducted to explore the pharmacological effects of snake fruit skin as different preparations against DM. In this study, the effect of snake fruit skin extract (SFSE) on body weight and blood glucose levels induced by alloxan was tested on 25 male Wistar rats. All rats were initially induced with 5% alloxan (150 mg/kg BW) then after 48 hours were grouped into: control (Na-CMC 0.5%), standard (Metformin), SFSE-I (60 mg/200 gBW), SFSE -II (120 mg/200 gBW), and SFSE-III (240 mg/200 gBW). The treatment was given for 14 days. The results showed that the tendency for the highest blood glucose levels of about 333 mg/dl (after 28 days of treatment) was found in the control group, followed by SFSE-I (222 mg/dl), -II (205 mg/dl), -III (138 mg/dl), and the lowest in the standard group was about 129 mg/dl. Hence, it can be concluded that SFSE which has the best antihyperglycemic effect was obtained with the highest dose of 240 mg/200 gBW.